Dietary antioxidants and risk of Parkinson's disease in two population‐based cohorts - Yang, Fei (Mov Disord, 2017)
Background: A neuroprotective effect of dietary antioxidants on Parkinson's disease (PD) risk has been suggested, but epidemiological evidence is limited. Objectives: To examine the associations between intake of dietary antioxidant vitamins and total antioxidant capacity and risk of PD. Methods: We prospectively assessed the relationships of dietary antioxidant vitamins C and E, ß‐carotene, and total antioxidant capacity with PD risk in two population‐based cohorts (38,937 women and 45,837 men). Results: During a mean 14.9‐year follow‐up period, 1,329 PD cases were identified. Dietary intake of ß‐carotene was associated with a lower risk of PD (hazard ratio: 0.86; 95% confidence interval: 0.78‐0.95; P (trend) < 0.01 for women and hazard ratio: 0.91; 95% confidence interval: 0.84‐0.99; P (trend) = 0.05 for men). An inverse association between dietary vitamin E and PD risk was found in women (hazard ratio: 0.87; 95% confidence interval: 0.79‐0.96; P (trend) = 0.02). Dietary intake of vitamin C was inversely associated with PD risk in women at borderline significance (hazard ratio: 0.91; 95% confidence interval: 0.83‐1.00; P (trend) = 0.04). There was no association between dietary total antioxidant capacity and PD risk in either women (hazard ratio: 0.93; 95% confidence interval: 0.84‐1.02; P (trend) = 0.35) or men (hazard ratio: 1.00; 95% confidence interval: 0.93‐1.07; P (trend) = 0.97). Conclusion: Intake of dietary vitamin E and ß‐carotene was associated with a lower risk of PD. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.